KAJIAN PARTISIPASI MASYARAKAT DAN PERAN PEMERINTAH DALAM KEGIATAN PENANGKARAN DAN KONSERVASI EKSITU RUSA TIMOR DI PROVINSI NUSA TENGGARA BARAT - M.M Budi Utomo; Rubangi Al Hasan (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2014)
Timor deer population in nature is declining, and therefore, the conservation is urgently needed. One form of conservation is exsitu conservation. Breeders society is one of the capital of ex-situ conservation. This research was conducted using the census of Timor deer breeders in the province. Interviews were conducted and questionnaires were prepared for data collection, which result then tabulated and analyzed descriptively. Results showed that people's participation in breeding is influenced by motivational factors, namely hobby and pride. Community participation in timor deer conservation efforts is low, caused by low level of understanding and awareness on the meaning of maximal conservation and limited role of government. It is recommended that the government seriously improve this situation in order to guarantee captive breeding be a successful conservation of timor deer in NTB.